Mitochondrial function in antarctic nototheniids with ND6 translocation - Mark, Felix C.; Lucassen, Magnus; Strobel, Anneli; Barrera Oro, Esteban; Koschnick, Nils; Zane, Lorenzo; Patarnello, Tomaso; Pörtner, Hans O.; Papetti, Chiara (PLoS ONE)
Fish of the suborder Notothenioidei have successfully radiated into the Southern Ocean and today comprise the dominant fish sub-order in Antarctic waters in terms of biomass and species abundance. During evolution in the cold and stable Antarctic climate, the Antarctic lineage of notothenioids developed several unique physiological adaptations, which make them extremely vulnerable to the rapid warming of Antarctic waters currently observed. Only recently, a further phenomenon exclusive to notothenioid fish was reported: the translocation of the mitochondrial gene encoding the NADH Dehydrogenase subunit 6 (ND6), an indispensable part of complex I in the mitochondrial electron transport system. This study investigated the potential physiological consequences of ND6 translocation for the function and thermal sensitivity of the electron transport system in isolated liver mitochondria of the two nototheniid species Notothenia coriiceps and Notothenia rossii, with special attention to the contributions of complex I (NADH DH) and complex II (Succinate DH) to oxidative phosphorylation. Furthermore, enzymatic activities of NADH:Cytochrome c Oxidoreductase and Cytochrome C Oxidase were measured in membrane-enriched tissue extracts. During acute thermal challenge (0-15°C), capacities of mitochondrial respiration and enzymatic function in the liver could only be increased until 9°C. Mitochondrial complex I (NADH Dehydrogenase) was fully functional but displayed a higher thermal sensitivity than the other complexes of the electron transport system, which may specifically result from its unique amino acid composition, revealing a lower degree of stability in notothenioids in general. We interpret the translocation of ND6 as functionally neutral but the change in amino acid sequence as adaptive and supportive of cold stenothermy in Antarctic nototheniids. From these findings, an enhanced sensitivity to ocean warming can be deduced for Antarctic notothenioid fish. Fil: Mark, Felix C. Alfred Wegener Institut; Alemania Fil: ...